Interactive Dustbin (International Journal of Engineering and Computer Science, 2015)
Nashik is a pilgrimage place and faces Kumbhmela in every 12 year. Being a place crowded with people, garbge disposal is a major problem. Lumping of garbage is found in city which may infect people and produce foul smell. Despite of creating awareness among the citizens, the waste is not yet being disposed in the bins provided by the Nashik Municipal Corporation. This paper brings to you an interactive solution for this, where people will anxiously participate in cleaning the city while they get some General knowledge.